Linguistic and non-linguistic features and functions of “bad language” by Malaysian netizens / Narsis Tayyebian - Tayyebian, Narsis (2015)

(untitled)
Bad language is one feature of language through which strong emotions such as anger, disgust, frustration and surprise is revealed. People use bad language which includes categories such as cursing, swearing, obscenity, blasphemy, profanity, obscenity, vulgarism, insults and slurs, epithets, slangs and scatology. All these categories vary in their themes in terms of the varying degrees of offensiveness. One of the contexts in which bad language occurs is the social media network sites such as Facebook which has become an important part of one’s daily lives since it is used as a common form of communication and interaction mode. Facebook is the media termed as technology of self because it is perceived as the site where people do things with words (Foucault cited in Basel, 2010). In this regard, Facebook can be seen as a representative site where appealing features of language use can be detected and in the context of this study, appealing features of bad language. This study aims to unravel the use of bad language by Malaysian netizens. Data were extracted from Facebook posts communicated among Malaysians from February 2013 to August 2014. Bad language used in Facebook page, “Only in Malaysia”, by Malaysian netizens as a way of expressing were extracted and then classified and categorized according to specific linguistic and non-linguistic features predominantly by using Thelwall’s (2008), McEnery’s (2005) and Anderson (2002) model. Moreover, the study aims to determine the types and functions of bad language based on the model proposed by Andersson, and Trudgill (1990). Using discourse analysis as an approach, this study also uses questionnaires and interviews to triangulate the methodology for a more comprehensive finding. The study reveals that bad language used among Malaysian users of English on Facebook has unique and distinctive aspects and features. It was found that the most favored taboo theme used by Malaysian netizens were those related to stupidity, animals and sexual relations. They were used mostly iv by the netizens as personal insult. This study also showed that Malaysians mostly prefer to use mild bad language for their various intentions and that the abusive functions denoted through the use of bad language was the result of anger.